Biofabrication of Reduced Graphene Oxide Nanosheets using Terminalia Bellirica Fruit Extract - B. Maddinedi, Sireesh; K. Mandal, Badal (Current Nanoscience, 2016)
Background: Graphene, a single atom thickness two dimensional material, has been considered as a promising material in nanoscience and nanotechnology due to its extraordinary optical, electronic, catalytic and mechanical properties. Green synthesis of graphene is of importance because of its low cost, simplicity in preparation and its aqueous dispersibility. The present work describes the use of T. bellirica fruit (pericarp) aqueous extracts as green reducing and stabilizing agent for graphene synthesis from graphene oxide (GO). Further, the prepared graphene was characterized by using different spectroscopic and microscopic techniques. Finally, the manuscript describes the possible mechanism for the stabilization of graphene by the plant polyphenols. Methods: GO was prepared by following a modified Hummers method. Reduced graphene oxide (RGO) was prepared from GO using T. bellirica (pericarp) aqueous extracts. Further, the synthesized RGO was characterized using UVVisible, XRD, SEM, TEM and FTIR techniques. Results: The prepared T. bellirica reduced graphene oxide (TBG) was characterized by using various instrumental techniques. UV-Visible and XRD have indicated conversion of GO to RGO. SEM and HR-TEM images have showed the thin, transparent and silk like appearance of TBG. Further, FTIR analysis has represented the participation of polyphenolic hydroxyl groups of T. bellirica extract in the reduction of GO to RGO and subsequent stabilization of RGO by oxidised polyphenols via π-π stacking interactions. Additionally, the band gap of TBG was calculated as 3.75 eV by DRS analysis. Conclusion: This work has shown a facile, low-cost, ecofriendly synthetic method for the production of reduced graphene oxide by using polyphenols from T. bellirica fruit extracts. FTIR analysis has concluded that the naturally occurring polyphenols present in T. bellirica extract are responsible for the reduction and stabilization of TBG. This paper further shows an eco-friendly method to produce RGO in bulk scale by using low cost polyphenols rich plant extracts.
Keywords: stabilization